FOREST RESOURCES AS A FACTOR OF STRATEGIC ADVANTAGE IN THE GEOPOLITICAL COMPETITION OF MAJOR ACTORS OF WORLD POLITICS IN THE CONTEXT OF GLOBAL CLIMATE CHANGE - Ivanok, Dmytro (Public Management and Policy, 2026)
The article provides a comprehensive analysis of the transformation of forest resources into an instrument of geopolitical competition in the context of global climatic and economic changes. The study aims to determine the role of forest resources as a factor of geopolitical influence of key actors in the international system and to establish the mechanisms through which they are employed in the implementation of foreign policy strategies within contemporary climatic and regulatory regimes. The methodological basis comprises institutional-comparative and comparative approaches combining the analysis of international regulatory documents, carbon regulation systems, and state climate policies. Content analysis, institutional analysis, and etymologization of geopolitical strategies were applied, enabling an examination of the interrelationship between forest resources, climate mechanisms, and the global redistribution of influence. The principal findings consist in the identification of a multilevel system of forest resource utilization in geopolitical competition, wherein key actors employ diverse models of influence – ranging from institutional norm-setting to resource and investment expansion. It is established that the geopolitical motivations of key actors in their use of forest resources are determined not by ecological priorities but by the logic of competition for influence and strategic advantage. The United States seeks to preserve its role as the architect of the global climate order, since control over the rules governing carbon markets provides an indirect means of shaping the economic behavior of other states. China employs forest and climate mechanisms to construct financial dependencies that are subsequently converted into political loyalty and an erosion of Western influence. Russia transforms forest resources and carbon schemes into geopolitical currency, exchanging them for a reduction in sanctions pressure and support for its own foreign policy ambitions. The European Union, Canada, and Japan, for their part, demonstrate that adherence to ecological norms simultaneously constitutes a source of normative influence and a structural constraint that narrows their geopolitical maneuvering space relative to actors that disregard such limitations. The geopolitical behavior of each actor in the domain of forest resources is subordinate to its broader foreign policy objectives. The global climate architecture does not eliminate geopolitical competition over forests; rather, it transforms its form – shifting the contest from the field of direct resource control to the arena of norm-setting, verification, and access to financial flows. It is precisely this tension between declared ecological goals and the actual geopolitical motivations of key actors that constitutes the central subject of this study. The scientific novelty lies in deepening the theoretical understanding of forest resources as an element of geopolitical power rather than merely an object of natural resource management, as well as in the systematization of the mechanisms through which they are deployed in processes of influence redistribution among key geopolitical actors. The practical significance of the findings lies in their potential application to the modelling of the geopolitical behavior of key actors in international politics. The particular scholarly value of the study derives from its interdisciplinary character – specifically, its integration of the international environmental dimension (the global struggle against climate change) and a geoeconomics framework, both of which generate new opportunities while simultaneously imposing significant constraints on geopolitical actors in the pursuit of their strategic objectives.